Hemoglobin Nanocrystals for Drugs Free, Synergistic Theranostics of Colon Tumor. Issue 8 (12th December 2022) - Zhou, Renbin; Xu, Hao; Qu, Junle; Ohulchanskyy, Tymish Y.
Abstract: The conventional approach in cancer nanomedicine involves advanced drug nanocarriers delivering preloaded therapeutics to targeted tumor sites to maximize drug efficiency. However, both cancer drugs and nanocarriers inevitably produce side effects and systemic toxicity. Herein, hemoglobin nanocrystals (HbC) as drug‐free theranostic nanoformulations with the tumor microenvironment (TME) activated diagnostic and therapeutic abilities towards colon tumors are introduced. HbC can release Fe 2+ oxidized to Fe 3+ in the Fenton reaction with tumor endogenous H2 O2, concurrently with the generation of cytotoxic hydroxyl radicals (OH) that allow for chemodynamic therapy (CDT). Furthermore, in situ‐produced Fe 3+ reacts with colon tumor‐abundant H2 S, resulting in the production of Fe1− x S, which provides magnetic resonance imaging (MRI) contrast and allows for NIR light‐inducible photothermal therapy (PTT). In vitro and in vivo studies revealed that HbC produced CDT towards 4T1 tumors, and MRI‐guided, synergistically enhanced combination of CDT and PTT against H2 S abundant colon tumors (CT26), with negligible toxicity towards normal tissues, enlightening HbC as highly efficient and biocompatible TME activated theranostic nanoplatform specific against colon cancer without any traditional drugs and drug carriers. Abstract : A drug free theranostic platform based on hemoglobin nanocrystals (HbC) is proposed for precise colon tumor diagnosis and treatment. HbC undergoes a Fenton reaction with tumor microenvironment specific H2 O2, producing OH for chemodynamic therapy (CDT). Simultaneously, colon tumor specific H2 S reacts with HbC to form Fe1− x S in situ for magnetic resonance imaging (MRI) guided photothermal therapy (PTT).